An experimental comparative analysis of the appropriateness of different sensible heat storage materials for solar cooking. (May 2023) - Saxena, Abhishek; Joshi, Sanjeev Kumar; Gupta, Parul; Tirth, Vineet; Suryavanshi, Ajay; Singh, Desh Bandhu; Sethi, Muneesh
Abstract: Solar energy is a significant energy source of outstanding sustainability, mainly used for heating and power production. There are numerous energy storage materials through which the performance enhancement of different solar heating systems is possible. In the present work, three different sensible heat storage materials, such as blackened pebbles, small pieces of masonry bricks, and small aluminium balls, have been experimentally studied for their thermal storage capacity inside a hot box cooker. All these materials have been used over the cooking plate of the tested cookers. Only three configurations have been developed to perform the stagnation and sensible heat tests. Notably, the authors have focused on a low-cost solution to enhance the thermal efficiency of a box cooker using sensible heat storage materials, especially for people from remote or rural areas. Even, a less educated consumer can easily apply the suggested technique to a box cooker through the Do-It-Yourself method. Results of the cooking trials have been found in favour of consumers and show the appropriateness of low-cost energy storage materials. These results also indicate a possibility of adopting all the tested models, mainly the cooker with aluminium balls, which is the best-configured cooker. This cooker has a thermal efficiency of about 59.61 %, cooking power of about 75.21 W, and thermal storage capacity of around 09 h/day. The estimated cost is approximately $47.06 for the best-configured cooker and its payback period is about 3.11 years. Highlights: Three different low-cost sensible energy materials are tested for solar cooking trails. All the modified cookers have excellent cooking performance and found capable for evening cooking. All the modifications can be made to the cooker by Do-It-Yourself by its users at low-cost. The best model has thermal efficiency about 59.61 % and cooking power about 75.21 W.